Diversity of Feeding in Anthozoa (Cnidaria): A Systematic Review - Barbosa Santos, Thais (2020)
In this study, we performed a bibliographical review examining the scientific literature on “feeding in Anthozoa” for the period from 1890 to 2019, using the scientific database Google Scholar, supplemented with additional literature. This study categorized published scientific papers on this topic by decade of publication, target taxa, variability of species studied in each order and main themes studied. As a result, 153 studies were found, and based on their content, it was observed that within Anthozoa, there has been a concentration of feeding studies on species in the orders Actiniaria (Hexacorallia), Scleractinia (Hexacorallia), and Alcyonacea (Octocorallia). This indicates that the other remaining orders of the group have been comparatively neglected with regards to their feeding aspects. Therefore, as data on feeding in some groups of Anthozoa are scarce, studies need to be carried out to fill the gaps that permeate this important benthic group, in order to better understand their ecology.